Concept Of Small And Medium Entrepreneurs In Customer Oriented Islam - Sari, Erni Nilam (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
For a Muslim entrepreneur, building a business is not just about getting profit, but how the business is run to meet the interests of customers. So there is more attention about how to treat customers. This study aims to examine how the interests of customers are met so that loyalty is born in purchasing by paying attention to the factors that influence it, namely the Islamic entrepreneurial spirit, business capital, and location. To answer the purpose of this study, the researchers used a quantitative approach with statistical regression analysis. The place of research was carried out in MSME Production of Typical Souvenir Cakes in Tulungagung. The research data was collected primarily with a questionnaire distribution technique. The results of the study concluded that customer purchase loyalty is strongly influenced by several factors, including the Islamic attitude of business actors. Honest behavior, responsibility, and maintaining the good values ​​of religion in trading can be added values ​​and affect customer ratings. Likewise, capital adequacy and business location can strengthen the business, and give a positive impression to customers.